Australia’s Long-Term Plankton Observations: The Integrated Marine Observing System National Reference Station Network - Eriksen, Ruth S.; Davies, Claire H.; Bonham, Pru; Coman, Frank E.; Edgar, Steven; McEnnulty, Felicity R.; McLeod, David; Miller, Margaret J.; Rochester, Wayne; Slotwinski, Anita; Tonks, Mark L.; Uribe-Palomino, Julian; et al. (Frontiers in Marine Science, 2019)
The Integrated Marine Observing System National Reference Station network provides unprecedented open access to species-level phytoplankton and zooplankton data for researchers, managers and policy makers interested in resource condition, and detecting and understanding the magnitude and time-scales of change in our marine environment. We describe how to access spatial and temporal plankton data collected from the seven reference stations located around the Australian coastline, and a summary of the associated physical and chemical parameters measured that help in the interpretation of plankton data. Details on the rationale for site locations, sampling methodologies and laboratory analysis protocols are provided to assist with use of the data, and design of complimentary investigations. Information on taxonomic entities reported in the plankton database, and changes in taxonomic nomenclature and other issues that may affect data interpretation, are included. Data from more than 1250 plankton samples are freely available via the Australian Ocean Data Network portal and we encourage uptake and use of this continental-scale dataset, giving summaries of data currently available and some practical applications. The full methods manual that includes sampling and analysis protocols for the Integrated Marine Observing System Biogeochemical Operations can be found on-line.